Cada vez por única vez - Alberto Giordano (Cuadernos LIRICO)
This essay, in the manner of a reading journal, brings together a series of entries with circumstantial notes on various autobiographical texts (memoirs, diaries, essays, hybrid forms). Each entry points out a unique way in which certain writings of oneself, in addition to narrating or recording episodes of the author's life, configure the tones and rhythms of the emotional processes that drove the autobiographical exercise.